Acetylcholine activates a regenerative vasodilator mechanism that is sensitive to nitric oxide production - Barrera, Nelson P.; Márquez, Mónica; Muñoz-Uribe, Matías; Figueroa, Xavier F. (Frontiers in Physiology, 2025)
IntroductionThe conduction of changes in the diameter of arterioles plays an important role in the coordination of the blood flow distribution. The endothelium regulates vasomotor tone by generation of vasodilator signals, such as nitric oxide (NO) and endothelium-derived hyperpolarization (EDH). Endothelium-mediated vasodilator responses initiated in an arteriolar segment are conducted along the vessel length, which depends on the electrotonic spread of EDH signaling activated at the stimulation site, but, in contrast, the contribution of NO is controversial.MethodsWe used the mouse cremaster muscle microcirculation in vivo to analyze the participation of NO in the mechanisms involved in the conducted vasodilation observed in response to the stimulation of a short arteriolar segment with a pulse of acetylcholine (ACh), an endothelium-dependent vasodilator, or S-nitroso-N-acetylpenicillamine (SNAP), an NO donor.ResultsThe response to ACh spread along the entire vessel showing only a slight decay and, in contrast, the dilation evoked by SNAP was restricted to the stimulation site, independently of the magnitude of the response. Blockade of NO production with 100 μM NG-nitro-L-arginine methyl ester (LNAME) or 100 µM NG-nitro-L-arginine (L-NA) reduced the arteriolar resting diameter by 10%–12%, but the combined application of both blockers enhanced the basal vasoconstrictor tone by ∼38% and inhibited the local (∼45%) and conducted (∼20%–35%) responses initiated by ACh. Interestingly, the conduction of ACh-induced vasodilation increased along the vessel length in the presence of L-NAME and L-NA. In addition, blockade of endothelial cell hyperpolarization exclusively at the stimulation site through microsuperfusion of tetraethylammonium (TEA) inhibited the local vasodilation, but not the conduction of the response.ConclusionThese results suggest that ACh activates an NO sensitive mechanism of regenerative propagation of vasodilator responses, which contributes to our understanding of microvascular function and the complex integration of endothelial signaling pathways in the coordination of the blood flow distribution.